570 The effects of 6-weeks program of physical therapeutic exergames on cognitive flexibility focused by reaction times in relation to manual and podal motor abilities (Balneo and PRM Research Journal, 2024)
The main purpose of the study was to identify the level of improvement in cognitive flexibility manifested by choice and cognition reaction times in relation to manual and podal skills as a result of the implementation of a program of therapeutic exergame exercises, for a time interval of 6 weeks at the level of students. 511 students participated in the cross-sectional study, of which 279 male (54.6%) and 232 female (45.4%), divided into two groups: the experimental group 266 (521%) subjects and the control group 245 (48%) subjects. The implementation of the experimental program comprising of 8 physical therapeutic exergames took place for 6 weeks, in one session per week, within the physical education lessons, only for the male and female experimental groups. In the initial and final testing session, 2 standardized tests were applied: TMT part A, B and 2 tests adapted for this study: Square Test and 25 Squares Test. The progress registered by the male and female experimental groups was statistically significant. In all tests, the experimental groups showed higher progress compared to the control groups. Depending on the gender differences, it was found that the male experimental and control groups made better progress compared to the female groups in the following tests: TMT part A, Square Test, 25 Squares Tests. The implementation of a physical therapeutic exergame program determined the improvement of cognitive flexibility manifested by choice and cognitive reaction times in conditions of manual and podal motor skills, demonstrating the effectiveness of exergame technologies adapted and implemented for prophylactic purposes.